The Role of Homeopathic Medicine in the Treatment of Acute Pharyngitis - Dr Meghaben Patel; Prof. Dr Yogita (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Acute pharyngitis, commonly characterized by inflammation of the pharynx, is often caused by viral or bacterial infections. The treatment of acute pharyngitis usually involves symptomatic relief, with the majority of cases being self-limiting. However, the increasing search for alternative therapeutic approaches has led to growing interest in homeopathic medicine. This article explores the role of homeopathy in the treatment of acute pharyngitis, evaluating its potential benefits, scientific basis, and clinical effectiveness. A review of current literature, as well as individual case reports, suggests that homeopathic remedies may offer symptom relief and accelerate recovery in acute pharyngitis cases, particularly in milder forms or as adjunctive therapy. Further research through randomized controlled trials is essential to establish the efficacy of homeopathy in this context.